Use of stable isotope signatures in the macroalga Ecklonia maxima and the filter feeder Mytilus galloprovincialis to determine the extent of sewage dispersal from the Green Point outfall, South Africa - Cyrus, Mark Digby (Department of Biological Sciences, 2017)
Over the last decade natural abundances of stable isotopes ¹³C and ¹⁵N have been used to investigate the transport pathways of nutrients within aquatic ecosystems, and have contributed new understanding and knowledge to many aspects of ecology, which include tracking the spatial extents of nutrient discharges. In order to assess the uptake of nutrients from the Green Point sewage outfall in Cape Town South Africa, we selected a primary producer, the kelp Ecklonia maxima (for dissolved nutrients) and a filter-feeding organism, the blue mussel Mytilus galloprovincialis (for organic particulates). It was hypothesized that biota within close proximity of the outfall would have isotopic values (signatures) which were closer to the values recorded for sewage and that this signature would become weaker (more positive) with increasing distance from the outfall as the sewage would be diluted and dispersed. Results from our study indicated that the stable isotope abundances of biota near the outfall were significantly affected by sewage. Ecklonia maxima situated on the outfall itself had δ¹⁵N of 1.2±2.3‰, which was extremely depleted relative to our control (8.3±1.1‰), collected at Mauritzbaai. The δ¹⁵N recorded for raw sewage (0.4±0.4‰) was very similar to that of Ecklonia maxima situated on the outfall. Mytilus galloprovincialis were also affected by sewage organic matter however although the effects on the stable isotope abundances were less pronounced as they were relying on more than one source of food. The isotopic values recorded in this study demonstrated that sites which were in close proximity to the outfall and even those just within the study area were contaminated by sewage effluent. From this study we conclude that the δ¹⁵N signatures of Ecklonia maxima and Mytilus galloprovincialis in marine environments can provide a useful means of tracing sewage dispersal in well-mixed ocean conditions, where conventional methods may have failed to reveal the extent of dispersal.